Limiting sway for unnbraced steel frame with column bending on minor axis - Mahmood, Md. Tahir; Mirasa, Karim; Osman, Mohd.Hanim (Penerbit UTM Press, 1998)
The proposed method is presented for the design of multi-storey steel frames to limiting values of horizontal sway deflection. The frame is divided into statically determinate sub-frames by assuming points of contraflexture. Allowance for steelwork costs is then used, together with slope-deflection analysis, to derive equations for optimum design. This method is suitable for hand calculation. A series of rigid jointed unbraced steel frames was studied with column bending on minor axis. The accuracy of the design equation was found to be good by comparison with linear elastic computer analysis. Ultimate limit state and serviceability limit state were checked for the frames.